Digital Platforms in China and Europe: Legal Challenges - Yu. Kharitonova; L. Sannikova (BRICS Law Journal, 2021)
The paper considers the processes of platformatization of the economy and public government, which have become the last decade’s primary trend. Analysis of the digital markets in Russia, China, and Europe proved the dominance of the digital platforms of large technology companies. According to the authors, the concentration of market power in digital platforms threatens a competitive environment in digital markets. In this regard, the demand for antitrust regulation of their activities is justiﬁed. Another legal challenge arises concerning the trend of creating public services on the digital platforms of large technology companies. The paper analyzes China’s experience in the platformatization of legal proceedings, where the process of establishing online courts is conducted in close cooperation with the leading digital platforms of the PRC. In contrast to China, in Russia, the main focus is on combining public services, and information systems of various departments within a single platform to provide public services, with large technology companies acting as operators. Therefore, the authors conclude that it is necessary to strengthen legal mechanisms to protect citizens’ rights and interests during the digitization of public services – primarily citizens’ rights to data protection. The problems revealed demonstrate the necessity of a balanced approach to the legal regulation of digital platforms. While it is important to stimulate their development, it is necessary to limit the opportunities for violating the rights and interests of other participants in the digital environment.